Religious Education in Students at Darul Quran Al Karim Kindergarten - Mustofa, Fuadul; Ichsan, Ichsan (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2023)
Religious character education is an effort to realize in a person the religious values contained in the Al-Quran and Al-Hadith. The aim of this research is to determine the process of religious character education for Darul Koran Kindergarten students. The research method used is a qualitative approach. This research was carried out at Darul Qur'an Kindergarten. The research subjects were school principals, teachers and students. Determining the research object was carried out using appropriate sampling techniques. Data collection techniques were carried out through interviews, observation and documentation methods. The validity of this research data uses triangulation. Data analysis uses data reduction, data presentation, and data design/monitoring. From the research results, it can be concluded that the process of religious character education for Darul Koran Elementary School students is learning activities such as respecting parents and teachers, routine activities such as reading educational prayers, reading the Al-Quran. before studying, Friday worship meetings and midday prayers in congregation. “Ah, spontaneous actions such as discipline, example, and students always have the enthusiasm to behave religiously. Supporting factors include teacher support, parent support, shared commitment from the school community and adequate facilities.